A projekttervezés folyamatának költség-haszon elemzést fókuszba helyező bemutatása - Tenclinger Tímea (2015)
I have chosen the cost-benefit analysis as the topic of my thesis, because I am interested in the process of project realization and on the other hand project planning within the cost-benefit analysis is most suited to my studies, as a student in finance and accountig major. My thesis is designed to provide insight into the planning process of EU-funded projects and outline the structure of cost-benefit analysis, the most influential part of that process. In connection with the topic the first part of the thesis begins with the presentation of the operation at my workplace and within my internship place. To write about the process of project planning I define first the project and summarize the topics relevant general information about projects. In short, I am writing requirements to project management, I present surroundings, participants and stakeholders of the project and outline the project life cycle and within each project phase, and the construction of a complete project. After that I provide insight into the planning process of EU-funded projects at my internship place and based on my experience I present suggestions to improve this process. The second part of my thesis is a general description of the cost-benefit analysis, wherein I explain its role and present its structure and then I advert to the description of the project I have chosen. I write about the knowledge related to performance indicators which form the core of the cost-benefit analysis and I also write about the conditions of eligibilty in case of projects. I present the elements of the schedule, which is the product of the cost-benefit analysis in the project I have chosen and I present through this the process of making the cost-benefit analysis. First the configuration of the indicators of financial analysis to which the financial costs, financial incomings and financial residual value are required. After I convert to the calculation of economic indicators based on the estimation of economic costs and economic benefits. I complete the theme with the sensitivity analysis and risk analysis which are the last part of cost-benefit analysis. In my writings I highlight in several places that the most important factors for the realization of projects are the substantional preparation and planning. The well-prepared and designed projects have a better chance to be finished successful and they can have a better position when they compete for state aid or EU support which they need for their realization.